Rekonstruksi Lembaga Penyelesaian Sengketa Akad Pembiayaan Dengan Jaminan Hak Tanggungan Pasca Putusan Mahkamah Konstitusi Nomor 93/PUU-X/2012 - Nurul Musjtari, Dewi (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2016)
The purpose of this research is to know the reconstruction of dispute resolution institutions of financing agreement with mortgage guarantee interest in Islamic banking practices following the Ruling of the Constitutional Court Number 93 / PUU X / 2012. In addition to this, the importance of this research is to the development of Islamic banking institutions in Indonesia and economic law, particularly the law of Islamic economics. For researchers, the importance of this study is to realize the competence of researchers in developing science insightful of sharia law, especially law of syariah economic.The method in this research, using qualitative tradition, its operation carried out in accordance kostruktivisme paradigm. The relative position (stand point) the authors of the problem in this study at the level epiteme not as a participant but instead as an observer. Strategy Research carried out by the two strategies is the research library (Library Research). This study uses socio-legal rules governing studie.Technic data collection to secondary data obtained through library research and a legal document. The primary legal materials, consisting of Article 55 of Law No. 21/2008 and explanation, Article 39 of Law No. 30 /1999, Law No. 4/1996, Law No. 50/2009 Constitutional Court Decision No. 93/ PUU-X / 2012. Secondary law, consists of book-nail on the agreement (contract), Islamic banking, political law, legal theory, legal research methodology, journals. The primary data obtained as supporting data through research in the field (Field Research) with observations interviews which includes: 1) Law sanction institution: Judges Religion, Arbiter in Basyarnas, Staff Bagia Legal in Islamic Bank, Mediator in Bank Indonesia, Notary; 2) Role Occupant: Management Islamic Bank, Islamic Bank Customers, which is done by hermeneutics, sociology of law and phenomenology. Analisys data using qualitative descriptive analysis that describes the development of dispute resolution institutions guarantee security interest in Islamic banking practices after the Constitutional Court Decision 93/ PUU-X/2012. The Results from this study is the reconstruction of dispute resolution institutions of financing agreement with hak tanggungan guarantee interest in Islamic banking practices following the Ruling of the Constitutional Court Number 93/ PUU X / 2012 is resolving disputes financing agreement with mortgage guarantee through Parate Executie more effectively and efficiently in other words more beneficial for of the parties when compared to the settlement of disputes trough the assurance executorial title. However, for the preventive protection during the pre-contractual agreement prepared sharia Islamic banks needfully the deed of acknowledgement of financing manufacture (APP) agreed debtor. The parties are no longer glued to that in resolving disputes and guarantee rights dependents through judicial institutions and non litigation in the narrow sense, namely non litigation on consultation, banking mediation, arbitration through the National Sharia Board of Arbitration or other arbitration institution, but can also cover non-litigation processes such as consultation, negotiation (negotiation), conciliation, non judge mediation, expert opinion or assessment.